The effect of personal factors and situational factors on impulse buying on Tiket.com users in Indonesia - Fitri, Fatharani Aghnia; Millanyani, Heppy (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This study aims to examines the effect of personal factors and situational factors on impulse buying in the context of impulse tourism especially on Tiket.com users in Indonesia. The survey method was used, and questionnaires were distributed to Tiket.com users. A sample of 400 respondents and the data were analyzed using multiple regression analysis with the help of SPSS 26 version software. The findings reveal that impulse buying tendency (IBT), materialism (MT), use of credit cards (CCU), personal situation (PS), motivational activities by retailers (MAR), serendipity information (SI) have a positive and significant effect on impulsive buying among Tiket.com users in Indonesia. Higher level of IBT, MT, CCU, PS, MAR, and SI variables increase the impulse buying impulse purchases for Tiket.com users in Indonesia. However, the research shows that website quality (WQ) and product attributes (PA) have a negative and significant influence on impulsive buying. The shopping enjoyment tendency (SET) and scarcity (SC) have no effect on impulsive buying (IB) for Tiket.com users in Indonesia. Based on these findings, it is suggested that further studies be conducted utilizing the same model with various objects to compare impulse purchases among Online Travel Agent (OTA) users and provide new insights into consumer behaviour, along with explore other factors that influence impulse purchases.